2022
DOI: 10.1093/eep/dvac017
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicant exposures and sex-specific effects on epigenetic programming and cardiovascular health across generations

Abstract: Despite substantial strides in diagnosis and treatment, cardiovascular diseases (CVDs) continue to represent the leading cause of death in the US and around the world, resulting in significant morbidity and loss of productive years of life. It is increasingly evident that environmental exposures during early development can influence CVD risk across the life course. CVDs exhibit marked sexual dimorphism, but how sex interacts with environmental exposures to affect cardiovascular health is a critical and unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 258 publications
1
4
0
Order By: Relevance
“…In line with this, our previous study identified sex-specific effects of dieldrin on neuroinflammatory gene expression and the data here expand on that with sex-specific effects on DNA modification in genes with critical functions in glia (Gezer et al, 2020). More generally, these data add to evidence of the sex-specific nature of epigenetic responses to developmental exposures, reiterating the importance of considering sex when investigating the epigenetic mechanisms driving disease development (Svoboda et al, 2022b,Hilz and Gore, 2022,McCabe et al, 2017.…”
Section: Distinct Sex-specific Responses To Exposures May Underly Sex...supporting
confidence: 88%
“…In line with this, our previous study identified sex-specific effects of dieldrin on neuroinflammatory gene expression and the data here expand on that with sex-specific effects on DNA modification in genes with critical functions in glia (Gezer et al, 2020). More generally, these data add to evidence of the sex-specific nature of epigenetic responses to developmental exposures, reiterating the importance of considering sex when investigating the epigenetic mechanisms driving disease development (Svoboda et al, 2022b,Hilz and Gore, 2022,McCabe et al, 2017.…”
Section: Distinct Sex-specific Responses To Exposures May Underly Sex...supporting
confidence: 88%
“…These findings highlight the need to evaluate sex-specific effects in toxicoepigenetic studies. 52,53 A greater degree of DMR similarity was seen between exposure types, with 1-7% of total DMRs appearing in both Pb and DEHP-exposed tissues, depending on the sex and tissue ( Figure 2D ) . General trends in DMR directionality were not conserved across tissue types, adding complexity to comparisons of changes in DNAm patterns between target and surrogate tissues ( Figure 2E ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the need to evaluate sex-specific effects in toxicoepigenetic studies. 53 , 54 General trends in DMR directionality were also not conserved across tissue types ( Figure 2E ), adding complexity to comparisons of changes in DNAm patterns between target and surrogate tissues. Although the majority of DMRs in blood from DEHP-exposed male and female mice was largely hypermethylated (65% in both cases), DMRs in the corresponding target tissues displayed either an approximate even distribution of hyper- and hypomethylated DMRs (as in male cortex and female liver) or with a majority of DMRs that were hypomethylated (as in female cortex and male liver).…”
Section: Discussionmentioning
confidence: 99%